Locomotor-Based Learning to Improve Motor Skills of Elementary School Students - Ridwan Sudirman; Ira Arini (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
This research aims to improve the motor skills of elementary school students through locomotor-based learning at SDN 3 Cadasari, Pandeglang Regency. This research is a classroom action research model of Kemmis and Taggart, which consists of 2 cycles. The research subjects were 32 students, consisting of 18 women and 14 men. Data collection uses the checklist observation method. The data analysis technique uses qualitative descriptive techniques. Improving motor skills is said to be successful if the percentage of students' motor skills reaches 70% (criteria for being able to perform locomotor movements). The research results prove that the locomotor-based learning model can improve the gross motor skills of grade 2 elementary school students at SDN 3 Cadasari, Pandeglang Regency. This is proven by the increase in students' motor skills in cycle I for locomotor movements by 45%. In cycle II, locomotor movement increased by 85%. Based on the analysis above, cycle I and cycle II, it can be concluded that the locomotor learning model can improve the motor skills of grade 2 elementary school students.